CORPORATE SOCIAL RESPONTIBILITY (CSR) PADA PT. BANK NTB SYARIAH - Siti Salha Mazaya; Zainal Asikin; Ari Rahmad Hakim B.F (Commerce Law, 2021)
This study describes the regulation of Corporate Social Responsibility (CSR) of banking companies, as well as its practice at PT. Bank NTB Syariah. This study is a normative-empirical one with statute, conceptual, and sociological approaches. Results of this study show that the regulation regarding CSR refers to the Law No 40 of 2007 of Limited Company, the Government Regulation No 47 of 2012 of Social and Environmental Responsibility, and the Government Regulation No 54 of 2017 of Regional-Owned Enterprises. Those three regulation manage that companies must allocate 5% of their profit for Social and Envionmental Responsibility in the form of CSR. In the case of PT. Bank NTB Syariah, it has been providing social programs and activities as CSR for society, including education, religion, health, natural and non-natural disaster management, art, and culture.